Regional public goods in Asia and Europe. (Asian Development Bank, 2020)
As economies become more integrated, development challenges are becoming more transnational. The provision of regional public goods can help address such challenges in Asia. They can play an important role in sustainable economic development at the national and regional levels by addressing common issues across borders.